Dipeptidyl Peptidase (DPP)-IV Inhibitors with Antioxidant Potential Isolated from Natural Sources: A Novel Approach for the Management of Diabetes - Anand-Krishna Singh; Dhananjay Yadav; Neha Sharma; Jun-O Jin (Pharmaceuticals, 2021)
Type 2 diabetes mellitus (T2DM) is characterized by hyperglycemia that is predominantly caused by insulin resistance or impaired insulin secretion, along with disturbances in carbohydrate, fat and protein metabolism. Various therapeutic approaches have been used to treat diabetes, including improvement of insulin sensitivity, inhibition of gluconeogenesis, and decreasing glucose absorption from the intestines. Recently, a novel approach has emerged using dipeptidyl peptidase-IV (DPP-IV) inhibitors as a possible agent for the treatment of T2DM without producing any side effects, such as hypoglycemia and exhaustion of pancreatic β-cells. DPP-IV inhibitors improve hyperglycemic conditions by stabilizing the postprandial level of gut hormones such as glucagon-like peptide-1, and glucose-dependent insulinotropic polypeptides, which function as incretins to help upregulate insulin secretion and β-cell mass. In this review, we summarized DPP-IV inhibitors and their mechanism of inhibition, activities of those isolated from various natural sources, and their capacity to overcome oxidative stress in disease conditions.